Working Length Determination Using Cone-Beam Computed Tomography, Periapical Radiography and Electronic Apex Locator in Teeth with Apical Periodontitis: A Clinical Study - de Morais, André Luiz Gomide; de Alencar, Ana Helena Gonçalves; Estrela, Cyntia Rodrigues de Araújo; Decurcio, Daniel Almeida; Estrela, Carlos (Iranian Endodontic Journal, 2016)
Introduction: The purpose of this clinical study was to compare the accuracy of working length (WL) determination using cone-beam computed tomography (CBCT), conventional periapical radiographies and electronic apex locator. Methods and Materials: This study was conducted during root canal treatment of 19 patients with a total of 30 single-rooted teeth diagnosed with apical periodontitis. After taking the initial parallel periapical radiographies, the initial file was advanced into the canal until the WL was detected by the apex locator. Subsequently, the WL was measured and WL radiographies were taken with the file set in the canal. Afterwards, CBCT images were acquired. These three measurements were tabulated and compared and the data were analyzed using the Friedman test. The level of significance was set at 0.05. Results: The mean values for WL determination by electronic apex locator, periapical radiograph and CBCT images were 22.25, 22.43 and 22.65, respectively which was not statistically significant (P>0.05). Conclusion: Working length determination using CBCT images was precise when compared to radiographic method and electronic apex locator. Keywords: Apical Foramen; Cone-Beam Computed Tomography; Dental Radiography; Electronic Apex Locator; Tooth Apex